Association between urinary albumin-to-creatinine ratio and all-cause and cardiovascular-cause mortality among MASLD: NHANES 2001–2018 - Wang, Zhengjin; Chen, Zhangxin; Zhuang, Hanxu (Frontiers in Nutrition, 2025)
BackgroundUrinary albumin-to-creatinine ratio (UACR) is an established biomarker for assessing kidney damage, but recent studies suggest it may also reflect broader health risks. This study aimed to investigate the association between UACR and all-cause and cardiovascular disease (CVD)-cause mortality in patients with metabolic dysfunction-associated steatotic liver disease (MASLD).MethodsIn this prospective cohort study, we included sample of 3,412 MASLD enrolled in the National Health and Nutrition Examination Survey 2001–2018. The study population was divided into three different risk categories based on urinary UACR: low level (<4.67 mg/g), intermediate level (4.67–7.67 mg/g), and high level (7.68–30 mg/g). Cox proportional hazards models were used to estimate the hazard ratios (HR) for the association between UACR level and both all-cause and CVD-cause mortality. Restricted cubic spline (RCS) curve analysis was employed to assess the non-linear association between UACR and mortality. Kaplan-Meier (KM) survival curves were used to evaluate survival rates across UACR groups.ResultsThe study found that higher UACR levels, even within the normal range, were independently associated with increased risks of both all-cause and CVD-cause mortality. Each 1 mg/g increase in UACR was associated with a 4% higher risk of all-cause mortality (HR 1.04, 95% CI 1.03–1.05) and a 5% higher risk of cardiovascular mortality (HR 1.05, 95% CI 1.02–1.08). Compared with the low UACR group, high UACR both showed an increased all-cause mortality risk [HR, 2.69 (95% CI, 2.07–3.50)] and CVD-cause mortality risk [HR, 2.97 (95% CI, 1.76–4.99)]. RCS curve analysis revealed a non-linear positive correlation between UACR and both all-cause and CVD-cause mortality, identifying UACR thresholds of 7.467 mg/g for all-cause mortality and 7.195 mg/g for CVD-cause mortality. The KM survival curves confirmed that participants with lower UACR levels had higher survival rates.ConclusionElevated UACR levels within the normal range, are associated with increased all-cause and cardiovascular mortality in patients with MASLD. UACR may serve as a useful early biomarker for identifying individuals at higher risk of mortality, supporting more proactive clinical interventions to manage MASLD-related risks.